Biochemical Changes in Legume Leaves Infected by Species of Pseudocercospora - Raghu Ram, M.; Mallaiah, K. V. (Indian Forester, 1996)
In this paper the biochemical changes in legume leaves on non-crop plants have been studied and the results are described in detail.